The Large Deflection Solution of Circular Elastic Membrane under Composite Loads. Issue 1 (1st June 2022) - Zhou, Can; Fang, Shuting; Liu, Changjiang
Abstract: In this paper, the large deflection problem of axisymmetric isotropic elastic membranes subjected to the composite loads is studied. The Hencky transformation is extended and the general solution of large deflection of the membranes under the composite loads is obtained. The general solution is given in different forms in different values of loads. The obtained results of the numerical values of elastic characters can be applied in practice.